Sosialisasi Pencegahan Penularan Covid-19 dan Bantuan Penguatan Ekonomi Masyarakat Terdampak Kota Banda Aceh - Bunyamin Bunyamin; Lindawati Lindawati; Amalia Amalia; Mery Silviana; Dewi Maya Sari (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
The beginning of 2020 is a new challenge for all countries affected by Covid 19, including Indonesia. The number of cases that continues to grow is a public concern. Even so, there are still many people who do not care about the dangers of the virus. Not only physically and psychologically, this global case also affects the economic condition of the community. One of the communities affected by the economy due to the Covid-19 pandemic is the people of Surien Village, Banda Aceh. This service activity aims to disseminate the prevention of Covid-19 transmission and assistance to strengthen the economy of the affected community in Surien Village, Meuraxa District, Banda Aceh City. The method used is to educate the public about health protocols that have been issued by the government to prevent transmission of the corona virus. Socialization was carried out by practicing and distributing brochures containing detailed health protocols such as wearing masks, physical distance from crowds and proper and proper hand washing methods tucked into the basic needs assistance. The results of these activities provide a deeper understanding to the public about the importance of wearing masks and washing hands properly for the early prevention of the spread of Covid-19. Providing basic food assistance is very useful for strengthening the economy of people who tend to be unprivileged during the Covid-19 pandemic issue.